The determinants of company value in motion picture industry - Yu, Luyang (2016)
Nowadays, with the improvement of the living standard, watching movie has been an indispensable part of the normal life. At the same time, the movie industry has achieved more attention than before. To many investors, the film industry is a new speculation choice given its flexibility and high ROI. However, behind those glorious investing achievement, there are more film companies suffer defeat and close down suddenly. It’s hard to make selection among those companies because of the high amount of unpredictability. This paper is aimed at exploring the value relevant drivers for this specific industry—motion picture industry in order to understand it better. The paper examines if the determinants for box office and academic award created values for the selected 30 United Sate companies from motion picture industry from 1990 to 2015. Result shows that both above determinants generate a positive effect on the company value.